Distribution of Corrosion Attack in Chloride Exposed Concrete – Summary of Field Observations - Baral Kedar; Geiker Mette Rica; Øverli Jan Arve (Nordic Concrete Research)
Reinforcement corrosion is the main deterioration mechanism in chloride-exposed reinforced concrete (RC) structures. Depending on the moisture level, corrosion might initiate when aggressive agents like chloride ions reach the reinforcement surface. The propagation of active corrosion depends on both the moisture level and oxygen availability. Corrosion reduces the crosssectional area and ductility of reinforcement. Depending on the severity of the attack and the corrosion products at the interface, it can lead to cracking and spalling of the concrete, thereby modifying bond-slip behaviour. Knowledge of the distribution of corrosion attack is required for the structural assessment of existing marine-exposed RC structures to extend their service life. This paper summarises observations of corrosion distribution on rebars excavated from RC elements after long-term exposure.